Law Enforcement Against Scampage at Polda Jatim : Perspectives of Positive Law and Islamic Criminal Law - Nur Izzah, Naila (Pustaka Peradaban, 2024)
This article focuses on two main questions: (1) How is law enforcement against scampage crimes conducted during investigations by Polda Jatim from the perspective of positive law, and (2) How is law enforcement against scampage crimes from the perspective of Islamic criminal law. The research method used is empirical, with primary data obtained from interviews at Polda Jatim and secondary data from regulations, journals, and related articles. Data collection was conducted through interviews and documentation, then analyzed qualitatively with a deductive approach. The research findings indicate that law enforcement by the Cyber Unit of Ditreskrimsus Polda Jatim follows proper procedures. Preventive measures are carried out through cyber patrols, while repressive measures use Article 35 in conjunction with Article 51 Paragraph (1) of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 on Information and Electronic Transactions (ITE). From the perspective of Islamic criminal law, the applied sanctions resemble jarimah ta'zir, allowing judges to impose educational and corrective punishments. Artikel ini berfokus pada dua pertanyaan utama: (1) Bagaimana penegakan hukum terhadap kejahatan scampage dilakukan selama penyelidikan oleh Polda Jatim dari perspektif hukum positif, dan (2) Bagaimana penegakan hukum terhadap kejahatan scampage dari perspektif hukum pidana Islam. Metode penelitian yang digunakan adalah empiris, dengan data primer diperoleh dari wawancara di Polda Jatim dan data sekunder dari peraturan, jurnal, dan artikel terkait. Pengumpulan data dilakukan melalui wawancara dan dokumentasi, kemudian dianalisis secara kualitatif dengan pendekatan deduktif. Temuan penelitian menunjukkan bahwa penegakan hukum oleh Unit Cyber Ditreskrimsus Polda Jatim mengikuti prosedur yang tepat. Tindakan pencegahan dilakukan melalui patroli cyber, sementara tindakan represif menggunakan Pasal 35 juncto Pasal 51 Ayat (1) Undang-Undang No. 19 Tahun 2016 tentang Perubahan atas Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (ITE). Dari perspektif hukum pidana Islam, sanksi yang diterapkan menyerupai jarimah ta'zir, memungkinkan hakim untuk menjatuhkan hukuman yang bersifat edukatif dan korektif.